NovelKCNJ5Mutations in Sporadic Aldosterone-Producing Adenoma Reduce Kir3.4 Membrane Abundance - Chih‐Jen Cheng; Chih-Chien Sung; Sheng-Tang Wu; Yu-Chun Lin; Huey‐Kang Sytwu; Chou-Long Huang; Shih‐Hua Lin (2014)
Aldosterone-producing adenoma (APA) has been linked to mutations in the KCNJ5 gene encoding the inward-rectifying potassium (K(+)) Kir3.4 channel. These mutations abolish the K(+) selectivity of Kir3.4 and, consequently, cause sodium (Na(+)) leak, depolarized membrane potential, and nonsuppressible aldosterone secretion.Our objective was to investigate KCNJ5 mutations in patients with sporadic APA and the role of endogenous Kir3.4 in human adrenocortical cells.We screened the KCNJ5 gene from the adrenal adenomas of 69 Chinese patients with sporadic APA and functionally characterized novel Kir3.4 mutations.Thirty-seven percent (26 of 69) of our APA patients carried heterozygous somatic mutations in the KCNJ5 gene. Besides the most common G151R and L168R mutations, we identified a previously uncharacterized E145Q mutation and 2 novel mutations (R115W and E246G) in 6 patients. The E145Q mutant conducted a barium-insensitive Na(+)-leak current. The R115W and E246G mutants preserved barium-sensitive, K(+)-selective and Gβγ-activatable Kir3.4 currents, which were ∼30% and ∼15% of wild-type current, respectively. Biotinylation assays revealed markedly reduced membrane abundance of R115W and E246G mutants. All Kir3.4 mutants exerted dominant-negative effects on wild-type channels. Kir3.4 protein expression in APAs with the novel KCNJ5 mutation was significantly lower than those in APAs with wild-type KCNJ5 or Na(+)-leak KCNJ5 mutations. Inhibition of endogenous Kir3.4 by tertiapin-Q significantly depolarized membrane potential and increased CYP11B2 expression in human adrenocortical cells.Besides Na(+)-leak mutations, novel KCNJ5 mutations causing a reduction of surface and total abundance of Kir3.4 are also associated with sporadic APA. Basal Kir3.4 current is important to maintaining normal resting membrane potential and suppressing aldosterone synthesis in human adrenocortical cells.